Additional nutritional considerations for preconditioning beef calves. - Philipe Moriel (EDIS)
Calves can be preconditioned using a wide variety of supplemental feed ingredients. However, feed ingredient selection is not the only factor to consider during a preconditioning process. Increasing the protein supply to stressed, preconditioning beef steers led to greater growth performance, and increased immune response to vaccination during a 42-day preconditioning period. Producers should not reduce the frequency of concentrate supplementation during the entire preconditioning period as it might lead to poorer vaccine response and average daily gain (consequently, less calf value at sale). However, a gradual reduction of frequency of supplementation is a supplementation strategy that can overcome these negative effects on growth and immunity, and allows producers to save on feeding and labor costs without producing lighter calves that have weaker immune responses.